2015
DOI: 10.4103/2008-322x.163765
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 and Nitric Oxide levels in exudative age-related macular degeneration

Abstract: Purpose:To evaluate plasma levels of endothelin-1 (ET-1) and nitric oxide (NO) in patients with exudative age-related macular degeneration (AMD).Methods:In this study, ET-1 levels, as well as nitrite plus nitrate concentrations as an indicator of plasma NO level, were measured in the plasma of 20 subjects with exudative AMD and compared with 20 healthy age and sex matched controls.Results:Mean plasma ET-1 level was significantly higher in exudative AMD patients as compared to control subjects (0.35 ± 0.06 fmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Authors highlighted that this specific increase would reflect a severe vascular disturbance ( Machalińska et al, 2011 ). With respect to oxidative stress, Totan and coworkers showed the presence of increased Endothelin-1 (ET-1) and reduced Nitric Oxide (NO) plasmatic levels in AMD, suggesting an imbalance between vasoconstrictor and vasodilator agents, possibly reflecting either an endothelial dysfunction in AMD pathogenesis or a role of vasoconstriction in exudative AMD ( Totan et al, 2015 ). Another study showed significant elevation of serum concentrations of IL-1α, IL-1β, IL-4, IL-5, IL-10, IL-13, and IL-17 in AMD patients compared to control subjects ( Nassar et al, 2015 ).…”
Section: Retinal Diseases: the Mechanisms Behind Clinical Manifestatimentioning
confidence: 99%
“…Authors highlighted that this specific increase would reflect a severe vascular disturbance ( Machalińska et al, 2011 ). With respect to oxidative stress, Totan and coworkers showed the presence of increased Endothelin-1 (ET-1) and reduced Nitric Oxide (NO) plasmatic levels in AMD, suggesting an imbalance between vasoconstrictor and vasodilator agents, possibly reflecting either an endothelial dysfunction in AMD pathogenesis or a role of vasoconstriction in exudative AMD ( Totan et al, 2015 ). Another study showed significant elevation of serum concentrations of IL-1α, IL-1β, IL-4, IL-5, IL-10, IL-13, and IL-17 in AMD patients compared to control subjects ( Nassar et al, 2015 ).…”
Section: Retinal Diseases: the Mechanisms Behind Clinical Manifestatimentioning
confidence: 99%
“…Endothelial cells produce a physiological balance of vasoactive substances to regulate vascular function, such as the vasoconstrictor endothelin-1 (ET-1) and the vasodilator nitric oxide (NO). ET-1 levels increase while NO availability decreases during aging, resulting in increased vasoconstriction and impaired vasodilation, which could lead to constriction of smaller vessels associated with ischemia of the choriocapillaris (decreased choroidal blood flow) seen in severe dry AMD (Stauffer et al, 2008; El Assar De La Fuente et al, 2012; Totan et al, 2015). Decreased choroidal blood flow in dry AMD has been correlated with severity of dry AMD, and could increase the risk for ischemia and hypoxia leading to choroidal neovascularization in wet AMD (Grunwald et al, 2005).…”
Section: Vascular Mechanisms In Choroidal Neovascularizationmentioning
confidence: 99%
“…Decreased choroidal blood flow in dry AMD has been correlated with severity of dry AMD, and could increase the risk for ischemia and hypoxia leading to choroidal neovascularization in wet AMD (Grunwald et al, 2005). Totan et al showed that patients with wet AMD exhibit increased ET-1 and decreased NO in the plasma, indicating that endothelial dysfunction is apparent in these patients (Totan et al, 2015). With age being the largest risk factor for AMD, it is not surprising that age-related vascular dysfunction would contribute to the progression of AMD, as seen also in a number of age-related diseases (Ehrlich et al, 2009; Akpek and Smith, 2013).…”
Section: Vascular Mechanisms In Choroidal Neovascularizationmentioning
confidence: 99%
“…Although the exact mechanism of AMD is still unknown, it has been established that advanced age is the main risk factor but that other factors could also be involved. These factors include cigarette smoking, elevated cholesterol levels, systemic arterial hypertension and stiffness, ultraviolet exposure, cardiovascular disease, race, gender and family history [77].…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%
“…A vascular theory, that includes abnormalities of the choroidal circulation has been suggested to contribute to AMD development [78]. Even though, the precise role of NO in the onset of AMD has not been clearly determined, the involvement of oxidative stress and NO as a part of the vascular theory has been reported [77]. Both factors (oxidative stress and NO alterations) can contribute to the vascularization decrease of choriocapillaris and apoptosis, to the increasing formation of drusen and to the increased VEGF release from the retinal pigment epithelium cells [79].…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%